The Crucial Role of Hygiene in Shaping Early Childhood Development: A Comprehensive Review - Prachi Shukla; Akanksha Singh; Sarita Srivastav; Suman Prasad (Archives of Current Research International, 2024)
In early childhood education, good hygiene habits are crucial. It supports the child’s development of strength, activity, responsibility, self-assurance, and good performance in daily tasks. It’s possible that poor cleanliness poses a risk to early childhood development (ECD). The immune system impacts brain development and functioning. The immune system’s later functioning in adulthood is influenced by early childhood factors, including hygiene, and this has implications for susceptibility to neurodevelopmental and psychiatric problems. Pregnancy-related inflammatory events have the potential to directly contribute to CNS developmental issues, which have been linked to autism and schizophrenia.